Cross-section transmission electron microscopy of the ion implantation damage in annealed diamond - Nshingabigwi, Emmanuel Korawinga (My University, 2014)
Diamond with its outstanding and unique physical properties offers the opportunity to be used as semiconductor material in future device technologies. Promising ap- plications are, among others, high speed and high-power electronic devices working under extreme conditions, such as high temperature and harsh chemical environments. With respect to electronic applications, a controlled doping of the material is neces- sary which is preferably done by ion implantation. The ion implantation technique allows incorporation of foreign atoms at de¯ned depths and with controlled spatial distribution which is not achievable with other methods. However, the ion implanta- tion process is always connected with the formation of defects which compensate and trap charge carriers thus degrading the electrical behaviour. It is therefore essential to understand the nature of defects produced under various implantation conditions. In this respect, this study involves the investigation of the nature of the radiation damage produced during the multi-implantation of carbon ions in synthetic high- pressure, high-temperature (HPHT) type Ib diamond spread over a range of energies from 50 to 150 keV and °uences, using the cold-implantation-rapid-annealing (CIRA) routine. Single energy implantation of carbon ions in synthetic HPHT (type Ib), at room temperature, was also performed. Both ion milling and FIB (Focused Ion Beam) milling were used to prepare thin specimen for transmission electron micro- scope (TEM) analysis. The unimplanted, implanted and annealed samples were characterized using trans- mission electron microscopy based techniques and Raman spectroscopy. ii iii In unimplanted type Ia natural diamond, a high density of platelets, exhibiting the typical contrast of both edge-on and inclined platelets on f100g planes was found. As-implanted HPHT type Ib diamond, implanted with single energy of 150 keV car- bon ions and °uence of 7£1015 ions cm¡2 revealed an amorphous diamond layer of about 80 nm in thickness while, for low °uence implantations, the damaged diamond retained its crystallinity after annealing at 1600 K. In addition, damaged diamond transformed into disordered carbon comprising regions with bent (002) graphitic fringes and regions of amorphous carbon when high °uence, i.e., one above the amor- phization/graphitisation threshold were used followed by rapid thermal annealing at 1600 K. Furthermore, the interface between the implanted and annealed layer and the diamond substrate at the end of the range, showed diamond crystallites, inter- spersed between regions of amorphous carbon and partially graphitized carbon. This indicates that solid phase epitaxial recrystallization regrowth in diamond does not occur.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, June, 2013
Keywords: Ion implantation.; Diamonds - Effect of radiation on.; Electron microscopy.